2024
DOI: 10.1097/cm9.0000000000003029
|View full text |Cite
|
Sign up to set email alerts
|

Personalized treatment of well-differentiated gastric neuroendocrine tumors based on clinicopathological classification and grading: A multicenter retrospective study

Ju Huang,
Huimin Liu,
Dekun Yang
et al.

Abstract: Background: The incidence of well-differentiated gastric neuroendocrine tumors (G-NET) is increasing annually, and while they have a good prognosis and low mortality rate, their high recurrence rate makes treatment options controversial. This study aims to determine the relationship between individualized treatment plans and the recurrence of G-NET. Methods: We performed a multicenter, retrospective study of 94 patients with highly differentiated G-NET … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Notably, another recent multi-centric study on welldifferentiated gastric NENs (N = 94, median follow-up of 49 months) showed a recurrence rate of 14%; the most important parameters that served as indexes of recurrence comprised the pre-therapy level of gastrin and the choice of therapy. In this cohort, the lowest recurrence rates were found in subjects who were treated with somatostatin analogues (SSAs) (5%) and those who underwent an endoscopic submucosal dissection (10%) [22].…”
Section: Prognostic Markers and Multimodal Management Of Nensmentioning
confidence: 91%
“…Notably, another recent multi-centric study on welldifferentiated gastric NENs (N = 94, median follow-up of 49 months) showed a recurrence rate of 14%; the most important parameters that served as indexes of recurrence comprised the pre-therapy level of gastrin and the choice of therapy. In this cohort, the lowest recurrence rates were found in subjects who were treated with somatostatin analogues (SSAs) (5%) and those who underwent an endoscopic submucosal dissection (10%) [22].…”
Section: Prognostic Markers and Multimodal Management Of Nensmentioning
confidence: 91%